Given equation is
(2x+3) (3x+1) = (3x-1) (2x-1)
= 6x^{2} + 11x + 3
= 6x^{2} - 5x + 1
= 16x +2
16x = -2
x = -

7) If the equation 4x^{2}+x(p+1)+1=0 has exactly two equal roots, one of the value of p is

5

-3

0

3

Answer: D

Explanation:

Roots are equal if discriminant
b^{2} - 4ac = 0
In given equation:
(P+1)^{2} - 4.41 = 0
(p+1)^{2} = 16 = (4)^{2}
p+1 = +4, -4
p= 3 or - 5

8) A journey of 300 km takes two hours more when the speed of a care is reduced by 5km/hr. What is the original speed of the car?

30

40

70

80

Answer: A

Explanation:

Let the speed of the car is x km/hr. Then
Speed = distance/ time:

=2

=>

x^{2} - 5x - 750 = 0
x^{2} - 30x + 25x - 750 = 0
(x - 30) (x + 25) = 0
x =30 or x = -25
The negative value of x is inadmissible; therefore the speed of the car is 30 km/hr.